Proyecto de factibilidad para la creación de una Empresa de Servicio de Internet vehicular para la Ciudad de Loja - Villavicencio Cobos, Dario Francisco (2016)
To prepare the next project to be implemented is to create an "Enterprise Internet for vehicles" for the city of Loja as an alternative for city dwellers have a service that contribute to technological advance in a growing city. To start with the study of this project, has set an overall target called "Project feasibility for the creation of a service company vehicular internet for the city of Loja", which specific objectives which served as a guide raised to the study. Currently the internet service for vehicles in the city of Loja mostly is neglected since the service pleases this need are substitute services, implementation of an enterprise of internet services for all kinds of means of transport projects, the which will be located in the city center. This aims to provide an innovative service assisted with the best technology available in the market to achieve total customer satisfaction. To study the characteristics of the market and the variables that influence it, such as age, gender, income level, as well as the city, culture, customs, among others identified. statistical sampling whose size and sample selection was sufficient to obtain reliable results was used. It is noted that the sample to determine the total of existing vehicles was made in the city of Loja, which corresponds to 45,000 vehicles. The market survey indicates that 79% of the research population would be willing to make use of this new internet service in the city of Loja; which shows a good demand from them, by the use of the service will offer the company. To do this, the Service Plan proposes to position the company in the minds of consumers defining strategies that will optimally conquer much of the existing population in the city. The legal status of the company is a Limited Liability Company, as it allows to be integrated three or more partners who only respond by social obligations to the amount of their individual contributions. The company set up with the name, whose name will be "MUGIBOX" Cia. Ltda. The plan projects provide services with 2 employees to customer service, who in an average of 8 hours daily serve approximately 15 clients daily each Monday through Friday, a month will serve approximately 600 customers and 7,200 customers. For implementation and startup of this company's total investment of $ 125,719.91 is required. This value includes the acquisition of fixed assets, deferred assets and current assets for the operation. Fixed assets reach $ 81.044,00 invested; deferred tax assets reach the value of $ 33,681.25; and current assets $ 10.994,66. Total costs for the first year are $ 158,474.28. Each year is projected costs to increase by 4.55% (based on 2015 inflation), therefore the fifth year costs amounted to $ 181,895.91. For the first year the company will get more than $ 225.033,48 revenues, which are higher than the cost of the same year. Projected revenues for the next five years, 10% plan to increase each year (based on the increase of the fleet in Loja) reaching earning the fifth year of $ 258,292.20. Net income in the statement of income for the first year is $ 66,559.20 while for the fifth year these revenues increase reaching a value of $ 76,396.28. The financial evaluation of the project, reflect positive financial indicators. With a projection of 5 years, a Net Present Value of $ 13,661.45 and an IRR of 18.33% is obtained. The project requires sell $ 109,023.01 in the first year to be in balance. Within the sensitivity analysis presented greater uncertainty are the costs, so the analysis is effected by taking as parameters a 19.74% increase in costs and a decrease of 35.02% in revenue. For this project, the sensitivity values are positive and less than 1, therefore does not affect changes in income and costs decreased or increased by 19.74% and 35.02%, respectively; that is, the project is not sensitive to these changes as demonstrated by calculating other indices. By the results of the sensitivity index it shows that is less than one, meaning that the project is not sensitive to an increase of up to 19.74% in costs, but if it happens this percentage will be negative for this project, showing us that this project is feasible and the revenue side, it was considered a decrease of 35.02%, and according to these results the sensitivity index shows us that is less than one, meaning that the project is not sensitive to a decrease of up to 35.71% in revenue, but if it happens this percentage will be negative for this project, showing the results obtained by that is feasible. The financial indicators are positive for investors of this project, therefore it is advisable to invest and start it.